Answer:
- sin = √(1 -cos²)
- tan = (√(1 -cos²))/cos
Explanation:
![\displaystyle\sin^2{\theta}+\cos^2{\theta}=1 \qquad\text{Pythagorean identiy}\\\\sin(\theta)=\sqrt{1-\cos^2{\theta}} \qquad\text{solved for sine}\\\\tan(\theta)=(sin(\theta))/(cos(\theta))=\frac{\sqrt{1-\cos^2{\theta}}}{cos(\theta)}](https://img.qammunity.org/2020/formulas/mathematics/college/1cup5mhxp8w0bizu7l0aqp9lczb0m2345f.png)
_____
If you draw a triangle with a hypotenuse of 1 and an "adjacent" leg of "cos", then using the Pythagorean theorem, you can see that the "opposite" leg will be √(1-cos²) and the tangent will be (√(1-cos²))/cos. Whether or not you're allowed to draw such a triangle on paper, you can certainly do it in your mind.